A combination therapy of ingredients from TCM for the prevention and treatment of gastric cancer by targeting HER2/ PD-L1 - Ling Li; Jia-wei Li; Xiao-jie Jin; Cheng-hao Li; Jun-jie Li; Ming Fang; Lu Qiu; Si-yu Wang; Wei Chu; Yong-qi Liu (Elsevier, 2021)
Gastric cancer (GC) is a globally important disease. Targeted therapies licensed to treat gastric cancer include trastuzumab, which targets HER2, and nivolumab or pembrolizumab, which block PD-1/PD-L1. The main challenge of tumor molecule-targeted drugs is resistance. Based on the multicomponent and multitarget characteristics of Traditional Chinese Medicine (TCM) and our previous research on Guiqi Baizhu Prescription (GQBZP) in targeting HER2/PD-L1, we used different cell models to verify the effect of quercetin targeting of HER2 and formononetin targeting of PD-L1. The results show that quercetin can inhibit MKN-45 cell proliferation by targeting HER2 to inhibit the PI3K-AKT pathway, and formononetin can regulate T-cell function by inhibiting the PD-1/PD-L1 pathway. We also used GC MKN-45 cells in a T lymphocyte co-culture model to show that quercetin and formononetin co-treatment can regulate T cell function and inhibit MKN-45 cell proliferation. More importantly, quercetin with formononetin treatment had a greater effect than treatment with either quercetin or formononetin alone. We believe that quercetin and formononetin may be useful to target HER2 and inhibit PD-1/PD-L1 in GC.